7 because if u add 4 and 3 that's what u end up with
The y-intercept of the equation is the value of the variable y or in this case, f(x), when x is equated to zero. Out of all the choices presented in this item, if x is equated to zero, the first two terms will be equal to zero, leaving the third term only for the numerical value of f(x).
From the choices presented, the answer would be f(x) = -x2 + 2x + 4. Thus, the answer is the third choice, C.
Answer:
$1,555.06
Step-by-step explanation:
Step-by-step explanation:
Given equation is
2y = 3x + 10
3x - 2y + 10 = 0 .....i)
Any line parallel to line I) is
3x - 2y + k = 0 ......ii)
As the line two passes through the point ( 2 , - 5 ) Now substituting the values
3 * 2 - 2 * ( - 5) + k = 0
6 + 10 + k = 0
16 + k = 0
k = - 16
Now putting the value of k in equation two
3x - 2y + 16 = 0 is the required equation.
Hope it will help :)❤
Answer:
3.5
Step-by-step explanation: